2003
DOI: 10.2337/diabetes.52.5.1229
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Fibronectin Overexpression Reduces Basement Membrane Thickening and Vascular Lesions in Retinas of Galactose-Fed Rats

Abstract: Overexpression of extracellular matrix (ECM) components is closely associated with the development of vascular basement membrane (BM) thickening, a histological hallmark of diabetic microangiopathy. To determine whether BM thickening of retinal capillaries could be prevented by down regulating synthesis of fibronectin, an ECM component, we used antisense oligos targeted against translation initiation site of the fibronectin transcript in galactose-fed rat, an animal model of diabetic retinopathy. After 2 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 33 publications
1
70
0
Order By: Relevance
“…Our findings indicated that CTGF is necessary for BL thickening and identified CTGF as a possible therapeutic target to prevent this early change in the retina caused by diabetes. That this may be a clinically relevant approach is indicated by recent studies that have shown that prevention of BL thickening can ameliorate the subsequent development of acellular capillaries in rodent models of diabetes (Roy et al 2003;Oshitari et al 2006). We detected a significant increase in particularly the endothelial cell BL in diabetic CTGF 1/1 mice compared with control CTGF 1/1 mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings indicated that CTGF is necessary for BL thickening and identified CTGF as a possible therapeutic target to prevent this early change in the retina caused by diabetes. That this may be a clinically relevant approach is indicated by recent studies that have shown that prevention of BL thickening can ameliorate the subsequent development of acellular capillaries in rodent models of diabetes (Roy et al 2003;Oshitari et al 2006). We detected a significant increase in particularly the endothelial cell BL in diabetic CTGF 1/1 mice compared with control CTGF 1/1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…BL thickening results from increased synthesis and/or decreased breakdown of its macromolecular components such as collagen type IV, fibronectin, and laminin (Roy et al 1994;Spirin et al 1999;Nishikawa et al 2000). Experimental prevention of BL thickening ameliorated early retinal vascular changes caused by diabetes (Roy et al 2003;Oshitari et al 2006). In galactose-fed rats, a model for type 2 diabetes, downregulation of fibronectin synthesis partly prevented retinal BL thickening but also reduced pericyte and endothelial cell loss (Roy et al 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oligonucleotides targeted against the translation initiation site of the fibronectin transcript have reduced fibronectin mRNA and protein level, and capillary basement membrane thickening in galactose-fed rats, another animal model of diabetic retinopathy [73]. Transfection of microvascular endothelial cells with AS-connexin 43 oligonucleotides is shown to inhibit glucose-induced alterations in intercellular communication and maintain vascular homeostasis [55].…”
Section: Antisense Treatment For Diabetic Retinopathymentioning
confidence: 99%
“…In vivo and in vitro studies have shown that diabetes selectively increases basement membrane gene expression in retinal vascular cells and that the excess synthesis of basement membrane components contributes, at least in part, to the development of thickened vascular basement membranes (6 -9). We have recently shown that the fibronectin antisense oligonucleotides (AS-oligos) reduce overexpression of basement membrane components and partially prevent the development of thickened vascular basement membrane in retinal capillaries of galactose-fed rats, an animal model of diabetic retinopathy, with beneficial consequences to histological lesions such as pericyte loss and acellularity (9). However, in order to completely prevent and reverse vascular basement membrane thickening, and regulate functional abnormalities, a more effective antisense strategy is necessary.…”
mentioning
confidence: 99%